Entrainment, detrainment, and large-scale horizontal gradients in oceanic deep convection - Stone, Rebecca E. (Monterey, California. Naval Postgraduate School, 1999)
The theory of oceanic convection and entrainment has been developed mainly in horizontally homogeneous regimes, yet large-scale spatial variability is known to control the sites and intensity of deep convection. Wintertime Greenland Sea conditions were selected to simulate convection and quantify the interplay between local forcing and large-scale gradients. Here circulation and preconditioning produce horizontal gradients in the stratification; some of the resulting stratification conducive to the formation of thermobaric convective instabilities. A large eddy simulation (LES) model modified to include large- scale horizontal density gradients was used to study the effects of the gradients on turbulence. Horizontal turbulent kinetic energy (IKE) and scalar variances increased compared to simulations with no large-scale gradient. The additional horizontal IKE is created at scales larger than the convective plume scale. A mean horizontal circulation develops in response to the large-scale overturning. The balance between convection and overturning increases stratification in the lower region of the mixed layer, and plumes may undergo slantwise convection. US Navy (USN) author http://archive.org/details/entrainmentdetra1094539421